Linguistic expressions of negative stances: A conversation analysis of turn-medial particle dai in Jishou dialect (Hunan Province, China) - Liu, Feng; Li, Xi; Liu, Rurong; Zeng, Jianyu (Frontiers in Psychology, 2023)
This paper, based on a corpus of 70 hours about 300000 characters of Jishou dialect in Hunan province, firstly analyzes the key syntactic functions and basic grammatical meanings of utterance-middle pragmatic particle dai from syntactic positions, utterance functions and prosodic features. Then, the paper tries to find out the distributions of dai in 7 different context quantitatively and applied the conversation analysis method to the dai related conversation qualitatively. The results demonstrate that dai is actually an overt marker of speakers’ negative affective stance for complaining and criticizing in conversation. Meanwhile, due to the effects of high frequency and speakers’ psychological cognition, also with the prosody, syntax, sequential positions, participants and interactional aims, etc., there are also speakers’ stance for sarcasm, surprise and sympathy arisen from dai though speakers’ complaints and criticisms exist in varying degrees. Based on analyses mentioned above, the present study attempts to reconceptualize the “particles” theoretically—that is, particles’ concrete meanings, discourse functions and syntactic structures integrate into a closely related whole in an interactive way. And being emergent products during the interaction, they interact also with diverse factors and are shaped continuously in talk-in-interaction. In addition, particles, as linguistic resources, provide participants with linguistic devices for managing and evaluating turns cooperatively to ensure the unfolding of current conversation.